Agreement Between Pregnant Individuals' Self-Report of Coronavirus Disease 2019 (COVID-19) Vaccination and Medical Record Documentation. Issue 6 (2nd December 2022) - Wielgosz, Kristina; Dawood, Fatimah S.; Stockwell, Melissa S.; Varner, Michael; Newes-Adeyi, Gabriella; Ellington, Sascha; Vargas, Celibell; Bruno, Ann M.; Powers, Emily; Morrill, Tyler; Reichle, Lawrence; Battarbee, Ashley N.; et al.
Abstract : There was a high level of agreement between self-reported and medical record–documented coronavirus disease 2019 (COVID-19) vaccination status among pregnant individuals. Abstract : For public health research such as vaccine uptake or effectiveness assessments, self-reported coronavirus disease 2019 (COVID-19) vaccination status may be a more efficient measure than verifying vaccination status from medical records if agreement between sources is high. We assessed agreement between self-reported and medical record–documented COVID-19 vaccination status among pregnant individuals followed in a cohort during August 2020–October 2021. At end of pregnancy, participants completed questionnaires about COVID-19 vaccine receipt during pregnancy; staff verified vaccination status using medical records. Agreement was assessed between self-reported and medical record vaccination status using Cohen's kappa. There was high agreement between self-reported and medical record vaccination status (Kappa coefficient=0.94, 95% CI 0.91–0.98), suggesting that self-report may be acceptable for ascertaining COVID-19 vaccination status during pregnancy.